Can Targeting Hypoxia-Mediated Acidification of the Bone Marrow Microenvironment Kill Myeloma Tumor Cells? - Gastelum, Gilberto; Veena, Mysore; Lyons, Kylee; Lamb, Christopher; Jacobs, Nicole; Yamada, Alexandra; Baibussinov, Alisher; Sarafyan, Martin; Shamis, Rebeka; Kraut, Jeffry; Frost, Patrick (Frontiers in Oncology, 2021)
Multiple myeloma (MM) is an incurable cancer arising from malignant plasma cells that engraft in the bone marrow (BM). It is known that the tumor microenvironment (TME) plays a critical role in MM development. These processes may be similar to what has been observed in the TME of other (non-hematological) solid tumors. It has been long reported that within the BM, vascular endothelial growth factor (VEGF), increased angiogenesis and microvessel density, and activation of hypoxia-induced transcription factors (HIF) are correlated with MM progression but despite a great deal of effort and some modest preclinical success using anti-angiogenic and hypoxia-targeting strategies, the overall clinical efficacy of these strategies has been limited. Thus, this review will explore this hypothesis that the TME of MM engrafted in the BM is distinct from that seen in non-hematological-derived solid tumors. Furthermore, we identify other hypoxia-mediated effectors, such as oxygen-dependent metabolic changes, generation of reactive oxygen species (ROS), and hypoxia-mediated acidification of the TME that may prove to be more effective targets against MM.